Structures and Spectroscopy Studies of Two M(II)-Phosphonate Coordination Polymers Based on Alkaline Earth Metals (M = Ba, Mg) - Kui-Rong Ma; Chun-Li Wei; Yu Zhang; Yu-He Kan; Ming-Hui Cong; Xiao-Jing Yang (Journal of Spectroscopy)
The two examples of alkaline-earth M(II)-phosphonate coordination polymers, [Ba2(L)(H2O)9]·3H2O (1) and [Mg1.5(H2O)9]·(L-H2)1.5·6H2O (2) (H4L = H2O3PCH2N(C4H8)NCH2PO3H2), N,N′-piperazinebis(methylenephosphonic acid), (L-H2 = O3PH2CHN(C4H8)NHCH2PO3) have been hydrothermally synthesized and characterized by elemental analysis, FT-IR, PXRD, TG-DSC, and single-crystal X-ray diffraction. Compound 1 possesses a 2D inorganic-organic alternate arrangement layer structure built from 1D inorganic chains through the piperazine bridge, in which the ligand L−4 shows two types of coordination modes reported rarely at the same time. In 1, both crystallographic distinct Ba(1) and Ba(2) ions adopt 8-coordination two caps and 9-coordination three caps triangular prism geometry structures, respectively. Compound 2 possesses a zero-dimensional mononuclear structure with two crystallographic distinct Mg(II) ions. Free metal cations   [MgO6]n2+ and uncoordinated anions (L-H2)n2- are joined together by static electric force. Results of photoluminescent measurement indicate three main emission bands centered at 300 nm, 378.5 nm, and 433 nm for 1 and 302 nm, 378 nm, and 434.5 nm for 2 (λex=235 nm), respectively. The high energy emissions could be derived from the intraligand π∗-n transition stations of H4L (310 nm and 382 nm, λex=235 nm), while the low energy emission (>400 nm) of 1-2 may be due to the coordination effect with metal(II) ions.